1999
DOI: 10.1152/jn.1999.82.3.1254
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Vestibuloocular Reflex Evoked by High-Acceleration Rotations in the Squirrel Monkey. I. Normal Responses

Abstract: The horizontal angular vestibuloocular reflex (VOR) evoked by high-frequency, high-acceleration rotations was studied in five squirrel monkeys with intact vestibular function. The VOR evoked by steps of acceleration in darkness (3,000 degrees /s(2) reaching a velocity of 150 degrees /s) began after a latency of 7.3 +/- 1.5 ms (mean +/- SD). Gain of the reflex during the acceleration was 14.2 +/- 5.2% greater than that measured once the plateau head velocity had been reached. A polynomial regression was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
137
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 45 publications
12
137
2
Order By: Relevance
“…In accordance with the model put forward by Minor et al (1999) for the monkey HVOR, we have suggested (Ris et al 2001b) that at high frequencies, type B MVNn might work in a nonlinear way, such as a signal detection mode, to amplify the contribution of vestibular nerve afferents. This should apply to guinea pigs because the HVOR dynamics and the way they are affected by UL appear roughly similar in all mammalian species Escudero et al 1993;Gilchrist et al 1998;Minor et al 1999;Smith and Curthoys 1989). Because our sinusoidal stimulations were designed to evoke only linear responses, the decrease of the firing rate modulation displayed by type B MVNn Ͼ4 Hz might result from the progressive involvement of nonlinear properties in the responses of type B MVNn at higher frequencies.…”
Section: Functional Implications Of the Long-term Changes Of The Membsupporting
confidence: 73%
“…In accordance with the model put forward by Minor et al (1999) for the monkey HVOR, we have suggested (Ris et al 2001b) that at high frequencies, type B MVNn might work in a nonlinear way, such as a signal detection mode, to amplify the contribution of vestibular nerve afferents. This should apply to guinea pigs because the HVOR dynamics and the way they are affected by UL appear roughly similar in all mammalian species Escudero et al 1993;Gilchrist et al 1998;Minor et al 1999;Smith and Curthoys 1989). Because our sinusoidal stimulations were designed to evoke only linear responses, the decrease of the firing rate modulation displayed by type B MVNn Ͼ4 Hz might result from the progressive involvement of nonlinear properties in the responses of type B MVNn at higher frequencies.…”
Section: Functional Implications Of the Long-term Changes Of The Membsupporting
confidence: 73%
“…Another difference in our study is we report VOR gain during the acceleration and constant velocity components of a step rotation. This is based on prior work in our laboratory, which has shown behavioral differentiation within the VOR pathway based on the acceleration (phasic component of the VOR which is accentuated at higher frequencies) and velocity (tonic component) content of the head motion (Minor et al 1999). We conducted VOR behavioral studies in squirrel monkeys and established that the phasic component of the VOR is larger during acceleration steps (G A ) than during constant velocity (G V ) rotation (Minor et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This is based on prior work in our laboratory, which has shown behavioral differentiation within the VOR pathway based on the acceleration (phasic component of the VOR which is accentuated at higher frequencies) and velocity (tonic component) content of the head motion (Minor et al 1999). We conducted VOR behavioral studies in squirrel monkeys and established that the phasic component of the VOR is larger during acceleration steps (G A ) than during constant velocity (G V ) rotation (Minor et al 1999). Clendaniel et al (2002) showed that the two components of the VOR pathway can be selectively modified by altering the frequency and velocity content of the adapting stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The gain and phase of the VOR in the light (VORl) and dark (VORd) have been well characterized for a range of head-perturbation frequencies in humans and non-human primates (e.g., Barr et al 1976;Correia et al 1985;Das et al 1998;Minor et al 1999;Paige 1983). These studies have shown that the gain of the VOR is higher when viewing a stationary target in the light than when imagining a target in complete darkness, suggesting cooperation between the VOR and visually mediated eye movements.…”
Section: Introductionmentioning
confidence: 99%